Regimes tributários na securitização de títulos e valores mobiliários: lucro real e lucro presumido - Fuso, Rafael Correia (2016)
This paper aims to study two taxation regimes for the activities of bonds or securities securitization: taxable income and presumed profit, taking into account these two regimes as liable to be adopted for this kind of securitization. We followed a path that seeks to define the securitization concept, investigated its legal nature, identified the legal relationships established between the parties involved in the process involving securitization companies, pointing out the securitization types that basically differ for each type of credit right. Leaving this generic part behind, we segregated sections of the legal regime, using the Law Science and the Legal Dogmatic to study in depth the bonds and securities securitization companies. We faced the problem of comparing the bonds and securities security companies with the factoring companies, indispensable to challenge the Brazilian Internal Revenue Service (Receita Federal do Brasil ) Regulatory Opinion number 5/2014. We identified all the differences between the business assets security companies and the factoring companies, concluding that only their means of acquisition and the credit rights are identical. Narrowing this paper’s focus, we analyzed in a generic way the taxes levied and not levied on the bonds and securities security companies. In order to use a scientific and useful criterion to discuss these taxes, not meaning that a different one could not be capable and important to investigate the tax levying, we built up the tax levying matrix rules. This tax investigation served as a premise to go on to the purposes of this paper, which is to analyze the taxation regime of the bonds and securities security companies, specifically the way of calculating taxes under the taxable income and presumed profit regimes integrating the calculation basis of the Corporate Income Tax (IRPJ), of the Net Profit Social Contribution (CSLL), of the Social Integration Program (PIS) and of the Social Security Financing Contribution (COFINS). This thesis main point relates to the tax regimes liable to be applied by the bonds and securities security companies through exploiting the problem of the federal tax authorities classifying these companies as being a species of the factoring activity, compelling them to submit to the taxable income regime, as provided by Law 9.718/1998, article 14, bringing legal uncertainty throughout the sector. We identified that during nine years the Brazilian IRS repeatedly stated and confirmed that the bonds and security securitization companies could (faculty) adopt collecting taxes under the presumed profit regime, as opposed to the federal tax authorities understanding in relation to the classification now being mentioned. Nevertheless, in April 2014 with the issuance of Ruling Opinion 5/2014 the IRS ended up changing its opinion, ignoring its past actions, interpreting Law 9.718/1998 art. 14, sub-item VI under the premise that as of the enactment of the mentioned law the business assets or bond and security securities companies should be submitted to the Taxable Income regime. We would like to emphasize that the consequence of this change was the write up of tax assessment notices against the bond and securities security companies, that started to face legal uncertainties. Notwithstanding this move to constitute tax credits, we found out that there were unconstitutionalities on the mentioned Ruling Opinion. In light of this legal instability caused by the Federal Government organ, many bond and security securities companies migrated to Credit Rights Investment Funds (FIDC). As a kind of securitization FIDC enjoys a simplified taxation way, keeping in its essence a similarity with the acquisition and assignment of credit rights submitted to rigid and specific legal rule and thus avoiding tax surprises perpetrated by the Public Power. Finally, due to growth, to tax simplifications and to the legal and operational feasibility to use receivables securitization through FIDC, legal movements and issuance of rules seeking the securitization of the delinquent tax debt recently started throughout the country. In light of the above, we investigated the legal feasibility of this securitization, pointing out the obstacles on its legal and underlying principles that in the present format without the necessary change of the legal regime, hamper the securitization of the delinquent tax debt of the political organs